A HYBRID SYSTEM FOR DYNAMIC ANALYSIS AND DESIGN OF COUPLED SHEAR WALLS (Sciences & Technology. A, exactes sciences, 2000)
Non-linear dynamic analysis techniques are rapidly being developed and have been recognized as indispensable tools. However, their use in the design office requires special experience. Consequently they are not generally accepted as analysis/design tools. Additionally, uncertainties are associated with the determination of the earthquake forces, the stiffness and strength of the structure; the selection of the mathematical models; and the form of the earthquake.In this paper a hybrid system for the non-linear dynamic analysis/design of coupled shear walls is briefly described. The system combines expert system technology with finite element method to carry out the dynamic analysis of coupled walls under earthquake forces. The system has been implemented using Quintec-Prolog, Quintec-Flex and FORTRAN 77, and runs on a SUN SPARC station under Unix system.